Kensuke's kingdom [videorecording (DVD)] - Cottrell Boyce, Frank; Morpurgo, Michael (Breaking Glass Pictures, 2025)
Based on the best-selling novel by Michael Morpurgo and adapted for screen by Frank Cottrell-Boyce, Kensuke's Kingdom spotlights the epic adventure of Michael, a young boy shipwrecked on a remote island who must adapt to life alone. Over time, Michael feels another presence and learns that his new world is home to both unimaginable danger and beauty.